A global value chain perspective on the phenomena of innovation and inequality. Issue 1 (2nd January 2022) - Biurrun, Antonio
ABSTRACT: The present brief comment explores some of Christopher Freeman's main ideas and their influence on my recent and current research. The concepts of broad and narrow National Systems of Innovation (NSI), regional systems of innovation and production networks are some of the main sources of inspiration for part of my works. Combined with a concern for development and social progress I have tried to understand how NSI relate and condition not only the outputs of innovation and economic growth but also their effect on social issues such as income inequality rates. Some evidence on the consequences of innovation on inequality is reviewed here, and some future lines of research regarding Global Value Chains (GVC) approaches are proposed.